The experiences of female ministers in counselling female rape survivors: A phenomenological study - Wyk, Neltjie C. van (HTS teologiese studies, 2018)
Rape is an act of humiliation that leaves the survivors ashamed. They therefore often try and hide from others and rarely seek help. Informal discussions with female ministers revealed that some of them had counselled female rape survivors. A descriptive phenomenological study, aimed at exploring and describing the experiences of female ministers in counselling female rape survivors through individual interviews, was conducted. Six ministers were interviewed. They experienced the dichotomy of being a woman and being a minister during their encounter with rape survivors. As women, they became emotionally involved in the suffering of the rape survivors, and as ministers they experienced that prayer and scripture reading in collaboration with counselling promote healing. They also experienced that rape survivors perceived them as approachable because of their gender, but less approachable because of their status as ministers.